Effect of Covid-19 On Oil Market - Al-Sulamy, Kholud Awadallah; Al-Amoudi, Khadija Mohammed (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this paper is to discuss the impact of COVID-19 on oil markets and mention the most important sectors that have been affected by the oil market in light of the impact of COVID-19. The authors use theoretical inductive approach to know what is the effect of COVID-19 on oil market, and What is the effect of changing oil prices on other industries after COVID-19. Lastly, how to face the risks of fluctuating oil prices? This study is important because on Monday 9 March 2020, Saudi Arabia announced a stunning discount in oil prices of $6 to $8 per barrel to its customers in Asia, the United States and Europe. After that Massive Discounts Oil prices and stock indexes were in freefall. Benchmark Brent crude oil futures dove 30%, the steepest drop since the Gulf War in 1991. A review of the literature shows that oil prices suffered an historic collapse. US oil prices crashed as much as 34% to a four-year low of $27.34 a barrel. Moreover, the impact of COVID-19 has extended to include Brent crude, Texas crude. Crude finished with a staggering loss of nearly 26% to settle at $31.13 a barrel. Brent crude, the global benchmark, plunged 24% to close at $33.36 a barrel. There is existence of a mutual effect between oil prices and some industries under the influence of COVID-19. For example, the aviation industry, and agricultural futures contracts. Also, it has been found that gold acts as a safe haven asset for international crude oil markets which can help investors to develop an effective portfolio strategy. Finally, the authors recommend future research to look into the precautionary processes that the markets should take to protect investor' money from any external factors that negatively affect it.
Keywords: oil market; COVID-19; Crude Oil